A review of the endoparasitic isopods (Epicaridea: Entoniscidae) from hermit crabs, including description of the new subfamily Diogenioninae and a new species of Paguritherium Reinhard, 1945 from the Philippines - Detorre, Marissa; Williams, Jason D.; Boyko, Christopher B. (Zootaxa, 2023)
Entoniscid isopods (Entoniscidae) are obligate endoparasites of other crustacean species. They have an indirect lifestyle, usually with two hosts and multiple larval stages; as adults they are found living within decapod hosts. Hermit crabs were previously known to be definitive hosts of only two species of entoniscid parasites: Paguritherium alatum, from the east coast of the United States in Pagurus spp. and Diogenion vermifactus from the Red Sea in Diogenes senex. Little beyond the original descriptions of these species has been reported in the literature. Recently, two species of entoniscids were found parasitizing hermit crabs (mostly Calcinus spp.) collected from shallow water coral reef areas in the Philippines. The goal of this study was to describe the morphology of both the adult and larval stages of these entoniscids through light and scanning electron microscopy and compare them to the previously described species that infest hermit crabs. One of these entoniscids is tentatively identified as D. vermifactus, which infested 0.95% (5 of 527) of the hermit crabs sampled. All specimens of D. cf. vermifactus were found in the abdomens of specimens of Calcinus gaimardii, C. minutus, C. pulcher and Pagurojacquesia polymorpha. Examination of D. vermifactus shows that this taxon belongs in its own subfamily: Diogenioninae n. subfam. The second entoniscid is a new species of the genus Paguritherium and infested 0.94% (7 of 744) of the hermit crabs (C. gaimardii and C. latens) sampled. Females of P. manggagaway n. sp. are characterized by a highly vaulted head, a slender body and long pleopods and males by a blunt head and stump-like pereopods covered in scales; the new species can be distinguished from P. alatum based on the specialized fan-like setae on the first five pereopods of the epicaridium larvae. A key to all entoniscid genera is provided.